MEKANISME DIVERSI TERHADAP ANAK PECANDU NARKOTIKA DITINJAU DARI UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Misbahul Ramadhany; Ifadah Hapsari (Jurnal Justiciabelen, 2021)
This research is entitled The Application of Diversion to Children of Narcotics Addicts in terms of Law Number 11 of 2012 concerning the Child Criminal Justice System. Furthermore, the formulation of the problems raised in this thesis are first, how to handle and procedure for giving diversion to children of Narcotics crime perpetrators in Gresik Regency. Second, whether the implementation of Diversion is in accordance with Law Number 11 of 2012 in Gresik Regency. Then the result of the research shows that the diversion mechanism for child offenders of narcotics offenses can be taken on several levels. The first level is the level of investigation in the form of deliberations among them: investigator deliberation, family deliberation and community deliberation. Furthermore, diversion must be carried out at every level of examination, both investigation, prosecution and trial, if the Diversion process is successful before the trial stage, the Investigator and Public Prosecutor will submit the results of the Diversion to the Head of the District Court to make an Determination and based on this Determination the Investigator and Public Prosecutor can issue SP3 (Letter of Order to Stop Investigation) and Decree of Termination of Prosecution. If the Diversion process succeeds in the trial stage, the Minutes and results of the Diversion shall be submitted to the Head of the District Court to make a decision on the termination of the case as for the legal action taken against the child who is a drug addict who fails to diversify, namely in the form of guidance